Analisis Kepemilikan Jamban dan Pengelolaan Sampah dengan Kejadian Stunting - Lega Bisa Diantara; Hilda Zulkifli; Hamzah Hasyim (Syntax Corporation, 2023)
Stunting is a global concern and is a target of the Sustainable Development Goals (SDGs). Stunting is caused by direct factors such as nutritional intake and infectious diseases as well as indirect factors such as sanitation, hygiene, food security and parenting styles. Where ownership of latrines and waste handling are part of sanitation. This study aims to analyze latrine ownership and waste handling with stunting incidents. This type of research is a quantitative study with a cross-sectional design. The population of this study were all children under five aged 0-59 months from the working area of the 11 Ilir Public Health Center, Palembang City, with a total of 301 people. Sampling was carried out by accidental random sampling and obtained a total sample of 102 respondents. Data collection was carried out using questionnaires, observation sheets to measure latrine ownership and waste handling and microtois to measure stunting. Data processing was carried out by univariate and bivariate analysis.Relationship between latrine ownership and the incidence of stunting (p value = 0.000) and the relationship between waste handling and stunting (p value = 0.000). There is a relationship between latrine ownership and waste handling with the incidence of stunting.